Effects of Ambidextrous Leadership on Employees’ Work Behavior: The Mediating Role of Psychological Empowerment - Wang, Li; Sun, Yuchen; Li, Jinzhi; Xu, Yunxia; Chen, Meifen; Zhu, Xiaoyu; Wang, Dawei (Frontiers in Psychology, 2022)
The complexity of today’s organizational environment increasingly requires leaders to think in a dynamic and flexible way to resolve contradictory issues. This study explored and compared the effects of servant leadership and authoritarian leadership on employees’ work behavior from the perspectives of ambidextrous leadership theory and social exchange theory, and further examined the mediating role of psychological empowerment. In this study, 315 employees from state-owned communication companies in Shandong and Zhejiang Provinces in China were selected as subjects, and path analysis was used to test the hypotheses. The results showed that servant leadership positively predicted organizational citizenship behavior and task performance. While authoritarian leadership negatively predicted organizational citizenship behavior and positively predicted task performance, psychological empowerment mediated the relationship between the two leadership styles and organizational citizenship behavior and task performance. Moreover, psychological empowerment and organizational citizenship behavior played a multiple mediating role between the two leadership styles and task performance. The theoretical implications of these findings for advancing the ambidextrous leadership theory in Chinese organizational contexts and practical approaches for corporate managers to effectively use ambidextrous leadership style were discussed.